Research progress on effect of ambient particulate matters on Alzheimer's disease and potential mechanisms - Lu YU; Chihang ZHANG; Jianshu GUO; Dongxia FAN; Jinzhuo ZHAO (环境与职业医学, 2025)
With the accelerating aging of world population, the prevalence and disease burden of dementia such as Alzheimer's disease is increasing annually. As one of the major risk factors for dementia, air pollution is still an urgent global concern. Studies on the association between ambient particulate matter (PM), one of the major air pollutants, and dementia, such as Alzheimer's disease, are gaining attention. This paper reviewed the current evidence of relevant epidemiological and toxicological studies to illustrate the possible mechanisms underlying the effects of PM exposure on Alzheimer's disease through inflammatory responses, oxidative stress, endocrine disruption, excitatory neurotoxicity, glial cell activation, and intestinal flora disruption, which may provide clues for mitigating the health risks of air pollution and preventing Alzheimer's disease.